Ոսկան Երեւանցին` Սաղմոսավանքի առաջնորդ - Աշոտ Մանուչարյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Деятельность архимандрита Воскана Ереванци в основном связана с армянским книгопечатанием и настоятельством в монастыре Уши. Но из одной купчей крепости выясняется, что он в 1661 г. был настоятелем монастыря Сагмосаванк. Здесь он в течение своего короткого духовного служения успел приобрести для монастыря право собственности на село Карвансара (ныне Арайи). Archimandrite Voskan of Yerevan is particularly noted for his works carried out in the publishing fi eld, as well as for his service as bishop in ordinary (or Ordinary Bishop?) in the monastery of Ushi. From one of the property papers we learn that in 1661 he used to be the bishop in ordinary of Saghmosavank. During the short period of his service he managed to get permission to make the village of Karvansara (nowadays Ara village) possession of the monastery.
Keywords: Biography; Auxiliary Sciences of History